2014
DOI: 10.1590/s1983-40632014000300011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial fisiológico de sementes de soja por meio de imagens

Abstract: A utilização de sementes com alto potencial fisiológico é de grande importância para agricultores, pois está, diretamente, relacionada à alta produtividade. Este estudo objetivou avaliar o desempenho de sementes de soja (cultivar CD 2737 RR) produzidas a partir de lotes com alta e baixa germinação, bem como a eficiência da análise computadorizada, pelos programas Seed Vigor Imaging System (SVIS®) e Tomato Analyzer, para identificar alterações no formato das sementes colhidas e associá-las com a germinação. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 6 publications
1
17
0
5
Order By: Relevance
“…Among the techniques available, X-ray analysis has been used to evaluate the internal morphology of seeds, making it possible to study the relationship between the occurrence of problems (mechanical damage, plant tissue malformation, and insect and microorganism damage) and physiological potential. Various studies have already been performed on seeds of different species and have shown the effectiveness of X-ray tests on identification of injuries associated with loss of germination, including studies on sweet corn (Gomes-Junior and Cicero, 2012), rice (Silva et al, 2014), and soybean (Wendt et al, 2014). In addition, X-ray images of seeds can be associated with other computerized image techniques for the purpose of increasing the effectiveness of seed analysis (Gomes-Junior, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Among the techniques available, X-ray analysis has been used to evaluate the internal morphology of seeds, making it possible to study the relationship between the occurrence of problems (mechanical damage, plant tissue malformation, and insect and microorganism damage) and physiological potential. Various studies have already been performed on seeds of different species and have shown the effectiveness of X-ray tests on identification of injuries associated with loss of germination, including studies on sweet corn (Gomes-Junior and Cicero, 2012), rice (Silva et al, 2014), and soybean (Wendt et al, 2014). In addition, X-ray images of seeds can be associated with other computerized image techniques for the purpose of increasing the effectiveness of seed analysis (Gomes-Junior, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds with 25% moisture content, for example, showed 96% germination. As observed by Holtz and Reis (2013) and Xavier et al (2015), this fact is usually related to the seeds storage in the field conditions, which ultimately affects not only the seeds physical quality but also physiological attributes such as germination, mainly due to the seeds exposure to fluctuations in temperature and relative humidity accelerating the deterioration. The relationship observed between germination and seed moisture content corroborated the results observed for the dry matter of seeds during maturation, since the largest dry matter accumulation occurred at the moisture contents of 55% (253.62 mg.seed -1 ), corresponding to the maximum germination potential of the seeds (Figure 2b).…”
Section: Resultsmentioning
confidence: 89%
“…Drying soybean seeds with moisture contents above 30% at temperatures of 50 °C increased the damage at the cellular level, particularly in the area of the embryonic axis of the soybean seeds (Silva et al, 2007;Afrakhteh et al, 2013), possibly because of its external location in the seed and the relatively thin protective tegument (Pinto et al, 2012). The development of normal seedlings perhaps was compromised by damage in the hypocotyl-radicle axis, which reduced the ability of the seeds to absorb reserves and produce vigorous seedlings (Surki et al, 2012;Wendt et al, 2014;Pereira et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations